Molecular Characterisation, Pathogenicity and Immunological Studies of Chicken Anaemia Virus Isolated In Malaysia - Chowdhury, Shah Md. Ziqrul Haq (2001)
A comprehensive study was carried out to isolate, identify and characterise chicken anaemia virus (CAV) isolated in Malaysia. The study resulted in the isolation of five CAV isolates from broiler chickens, designated as BL-1, BL-2, BL-3, BL-4 and BL-5. These isolates together with three isolates (SMSC-1, SMSC-2 and 3-1) provided by Veterinary Research Institute (VRI), Malaysia and a reference Cux-1 isolate were analysed by different restriction endonuclease enzymes. The whole genome of each CAV isolate was amplified by PCR into four fragments: Fragments A, B, C and D. Fragment A was digested with Styl, fragment B with StyI, Hpall and Mbol, fragment C with Haelll, and fragment 0 with EcoRI. The overall analysis revealed that the four isolates, BL-1, BL-2 , BL-4 and BL-5, exhibited the same restriction profiles in all enzymatic reactions and they are placed in one group, whereas, the other five isolates (SMSC-1, SMSC-2, 3-1, BL-3 and Cux-1) were found to be different from each other and also from the group of four isolates mentioned above. The pathogenicity studies in specific pathogen free (SPF) chickens inoculated with SMSC-1, 3-1 and BL-5 isolates at 1-day old showed that, the isolates produced clinical signs and characteristic lesions suggestive of CAV infection at 14-16 days post inoculation (p.L). The histopathological lesions in infected chicks showed severe depletion of lymphocytes from thymus, bursa and spleen and aplastic changes in bone marrow. The repeated passages of two VRI isolates, SMSC-1 and 3-1, in MSB1 cell line until passage sixty (P60), and passage 123 (P123), produced attenuated viruses (SMSC-1/P60, 3-1/P60. SMSC-1/P123 and 3-1/P123) which showed significantly reduced level of pathogenicity in SPF chickens compared to the pathogenic parent isolates. The whole genome of two non-attenuated isolates (SMSC-1 and 3-1) and two attenuated isolates (SMSC-1/P60 and 3-1/P60) were sequenced using the Perkin Elmer's BigDye Terminator Cycle Sequencing Kit. The high G:C regions of the CAV genome were sequenced using the same kit by the development of a modified method. The results showed that the complete genome of all isolates consisted of 2298 nucleotides. Three major ORFs of 1347 bp, 648 bp and 363 bp long were found in the plus DNA strand in all isolates, coding for putative proteins of about 52 kDa (VP1). 24 kDa (VP2) and 13 kDa (VP3). respectively. The alignment and antigenic index of VP1 sequence revealed the appearance of a hypervariable region from amino acid positions 139 to 157. The results showed that 76 nucleotide changes in SMSC-1/P60 and 43 nucleotide changes in 3-1/P60 isolates compared to their parent isolates, were thought to contribute to virus attenuation. Among these nucleotide changes, only one nucleotide difference (T-C) at position 816 resulted in changes of amino acid residues at positions 153 in VP2 from V to A, and 118 in VP3 from C to R. This single nucleotide change is probably important for the change in virus pathogenicity or attenuation. The phylogenetic analysis showed that the SMSC-1 isolate is close to the Australian 704 and Japanese TR20, the 3-1 isolate is close to the German Cux-1 isolate and the attenuated cloned isolate 10 (derived from the Cux-1). The attenuated SMSC-1/P60 and 3-1/P60 isolates were very close to the Japanese isolate A2. The apoptosis study carried out with electron microscopy and DNA fragmentation analysis, detected apoptosis both in infected thymocytes and infected MSB1 cells. The immunological studies with P1, P60 and P123 isolates of SMSC-1 and 3-1, and also with BL-5 isolate, after inoculation into 1-day-old SPF chickens showed that each of the isolates elicited CAY antibody responses, both at 14-16 days and 30 days p.i. Based on the findings of antibody response and pathogenicity studies, the attenuated isolates of P60 and P123 are potential candidates for live vaccines.